Handbook of valves and actuators - Nesbitt, Brian (Valves manual international., 2007)
Industries which use pumps, seals and pipes will almost certainly also use valves in their systems. Someone in each industry needs to be able to design, purchase or maintain the right valve for the job in hand, and that can amount to a lot of valves world-wide. Here is a single resource which is aimed at those designers and end users, plus their engineering staff. Brian Nesbitt is a well-known consultant with a considerable publishing record. A lifetime of experience backs up the huge amount of practical detail found in this volume. Its international approach is no accident: it will have world-wide take-up. *Ideal reference for industry *Practical approach compared with competition *Buyers' guide included.